2012
DOI: 10.1159/000338619
|View full text |Cite
|
Sign up to set email alerts
|

Distal Venous Arterialization and Reperfusion Injury: Focus on Oxidative Status

Abstract: In patients with unreconstructable arterial occlusive disease distal venous arterialization (DVA) seems to be a promising option in the treatment. The goals of this prospective study were to assess clinical efficiency and possible impact of DVA on tissue damage by estimating oxidative status of patients with critical limb ischemia treated with this procedure. The subjects were 60 randomized patients: 30 were undergoing DVA and 30 were treated with antiaggregation therapy. During the mean follow-up period (6.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…al., [8] indicates that there is no statistically significant reperfusion injury after this surgical procedure, confirming the validity in these patients because it achieved the therapeutically goal -adequate re-oxygenation of ischemic tissue.…”
Section: Distal Venous Arterialization (Dva)supporting
confidence: 56%
See 1 more Smart Citation
“…al., [8] indicates that there is no statistically significant reperfusion injury after this surgical procedure, confirming the validity in these patients because it achieved the therapeutically goal -adequate re-oxygenation of ischemic tissue.…”
Section: Distal Venous Arterialization (Dva)supporting
confidence: 56%
“…The aim of the present review is to display the role of those treatments and their level of success, reporting the effective ones in reducing the extension of the injury caused by reperfusion and its aspects [1,2,3,5,6,7,8,11,12,13,15,16,17,18].…”
mentioning
confidence: 99%
“…However, in the studies by Djoric et al 13% limb salvage was observed in those patients treated by conservative means, while 83% and 93% limb salvage was obtained in the venous arterialisation group. 15,16 These findings and the differences in limb salvage rates in the studies included here suggest that patient selection might be important. Unfortunately, there are no data robust enough to support any recommendation on how to appropriately select patients for either venous arterialisation or conservative treatment or amputation.…”
Section: Discussionmentioning
confidence: 79%
“…15,16,23 Four articles were comparative studies. 15,16,22,24 Three compared surgery with conservative treatment 15,16,22 and one compared venous arterialisation with pedal bypass. 24 The included and excluded studies are summarised in Table 1 and Table 2, respectively.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation